Da crise do estado à democracia como alvo: Observações sobre o neoliberalismo a partir de Friedrich Hayek e Milton Friedman - Ferreira, François de Oliveira (2009)
The neoliberalism proclaims the crisis of the State in front of globalization , but, approaching two books taken as basic on this theoretical chain - The road to serfdom, of Friedrich Hayek, and Capitalism and Freedom, of Milton Friedman - to analyze this supposed dualism, the conclusion into which we arrive is another one. Remembering liberal tradition and quickly, later, analyzing critically the workmanships, can be perceived that others are the conflicts really gifts in the current capitalist reality - market versus State et capitalism versus democracy - and, from the understanding on the reading made and the theoretical trajectory of its authors, we may see as the neoliberalism locates itself in relation to these conflicts, which polar regions of these antagonisms privileges, what represents the State for itself, and what it intends as much more global philosophy than economic/politics thinking only